New Information of the Anatomy and Phytochemical Screening of Pentaclethra macroloba (Willd.) Kuntze (Caesalpinioideae-Leguminosae) Seeds - Zelina Ataíde Correia; Ely Simone Cajueiro Gurgel; Olivia Ribeiro; Ana Cristina de Andrade Aguiar Dias; Ravendra Kumar; Luis Adriano Santos do Nascimento; Eloisa Helena de Aguiar Andrade; Mozaniel Santana de Oliveira (International Journal of Food Science)
Pentaclethra macroloba (Willd.), whose common name is “pracaxi,” is naturally found in the Amazon region. The present study is aimed at analyzing the anatomy, seed histochemistry, and chemical composition in fatty acid profile of P. macroloba seed oils. Seeds were collected in the cities of Belém, Marituba, and São Domingos do Capim-PA. For the study in light microscopy, scanning electron microscopy, and histochemistry, seeds were sectioned in cross and longitudinal sections of the embryonic axis and fixed in formaldehyde, acetic acid, and 50% ethyl alcohol; neutral-buffered formalin; and formaldehyde and ferrous sulfate and stored in 70% ethyl alcohol. For the anatomical study, the seeds were subjected to the usual techniques of plant anatomy. Histochemical tests were performed on plant material, freehand sectioned, and embedded in histological paraffin with DMSO. The fatty acid profile was determined for gas chromatography (GC-FID). Integument is divided into three strata, monoseriate exotesta, mesotesta formed by several layers of parenchyma cells, and monoseriate endotesta, formed by compressed cells. Cotyledons are composed of thin-walled parenchyma cells with several secretory cavities and secretory idioblasts. The main metabolic classes are lipids, phenolic compounds, carbohydrates, proteins, and alkaloids. The main fatty acids found in P. macroloba oil are oleic, behenic, lignoceric, and linoleic. P. macroloba seeds have important anatomical characteristics for their circumscription in Leguminosae and also in Caesalpinioideae, and their oil is rich in fatty acids essential to the human diet, providing many benefits to the human health, such as fatty acids belonging to the omega family (linoleic, oleic).